Diagnostic agreement between 3.0-T MRI sequences of nerve root and surgery in patients with cervical radiculopathy: A retrospective study. Issue 4 (29th January 2021) - Wang, Qi; Li, Huixia; Kong, Jianjun; Li, Xiaohui; Feng, Lin; Wu, Zhanyong
Abstract : Abstract: Currently, minute structures, such as cervical nerve roots, can be viewed using magnetic resonance imaging (MRI) sequences; however, studies comparing multiple sequences in the same set of patients are rare. The aim of the study is to compare the diagnostic values of three 3.0-T MRI sequences used in the imaging of cervical nerve roots. This study included 2 phases. In the first phase (n = 45 patients), the most optimal MRI sequence was determined. In the second phase, this MRI sequence was compared with surgical results (n = 31 patients). The three-dimensional double-echo steady-state (3D-DESS), multi-echo data image combination (MEDIC), and 3D sampling perfection with application-optimized contrasts using different flip angle evolutions (3D-SPACE) sequences were performed to analyze the image quality. Furthermore, the most optimal MRI sequence was compared with surgical results to determine the agreement rate. The image quality scores of the 3 sequences were significantly different ( P < .05). The score for 3D-DESS sequence was superior to that of MEDIC sequence, while the score for 3D-SPACE sequence was the worst. For visualization of compressed nerve roots, 3D-DESS sequence was superior to the other 2 sequences in terms of the total quality score and compressed nerve root score. Therefore, 3D-DESS sequence was used for MRI in 31 patients with cervical spondylosis in the second phase of this study. The diagnostic agreement rate was 93.5%. This study concluded that in patients with cervical radiculopathy, the 3D-DESS sequence is superior to the MEDIC and 3D-SPACE sequences and shows a high agreement rate with the surgical diagnosis.